The Influence of Work Motivation on Employee Job Satisfaction in The Pringsewu Regency Public Works Department - Muhammad Junaidi; Garaika Garaika; Fauzi Fauzi (eCo-Buss, 2021)
Human resources have an important role in every activity of the organization. For community service organizations to run, in line with expectations and to meet the needs of the community, the organization must have reliable and competitive human resources. Because it's good that an organization must be run by people who can manage existing resources to be effective and efficient so that it can make the organization competitive, creative and innovative. Organizational management must have a strategy in realizing human resources that can realize organizational goals. This study has a goal to be achieved, which is to know the effect of work motivation on employee job satisfaction at the Public Works Department of Pringsewu Regency. From the analysis of data processing for simple regression analysis, the results of the regression equation with Y = 30.887 + 0.476X2. The acquisition of statistical tests using the t-test on the variable work motivation of employees showed a value of a t-count of 5.357. The decision of the test, the t-value was 5.357. When compared to the prices of the t-student distribution table n = 44 at the real level of 0.05, a critical price of 1.671 is obtained> t-count> t table Conclusions Ho is rejected and Ha is accepted or employee work motivation variables are proven to have a significant effect on employee job satisfaction. The value of R Square (R2) is 0.406. This shows that the motivation variable influences 40% of employee job satisfaction, while the remaining 60.4% is the influence of other independent variables not explained by this research model. The relationship between motivation and job satisfaction was 63.7%”.